The snowy day - Keats, Ezra Jack. (Harmondsworth ; New York : Puffin Books, 1978)
The adventures of a little boy in the city on a very snowy day.
"Caldecott Award book."
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Caldecott Medal/Honor
3.2
K-3
Keywords: Snow -- Fiction; Afro-Americans -- Fiction; Snow -- Fiction; Caldecott Medal books